(untitled) (International Journal of Management and Sustainability, 2015)
Attention towards the agrirural social enterprise (SE) in Taiwan has increased, and optimisation for organisational performance has become crucial. Numerous agrirural service organisations have demonstrated their transforming intentions and potentials. In this study, a new self-report SE performance questionnaire, which is easy to administer and empirically valid, was developed. To explore the perceived performance of agrirural SE potential entrants, the agrirural SE performance can be assessed on the basis of four dimensions: personal issues, the social aspect, the business side, and service programmes. The results revealed that the length of time of engaging in SE predicted the three dimensions: personal issues, the social aspect, and the business side. The experience in operation function predicted the perceived performance of personal issues; the experiences in finance and accounting (F&A) and information system functions predicted the perceived performance of the social aspect and business side; and the experience in F&A function predicted the perceived performance of service programmes.